The LCC type DC grids forming method and fault ride-through strategy based on fault current limiters - Changlin Liu; Baohong Li; Yingmin Zhang; Qin Jiang; Tianqi Liu (International Journal of Electrical Power & Energy Systems)
With the integration of a large number of new energy sources into the power grid, the degree of multi power center continues to deepen, and multi-terminal DC transmission is receiving increasing attention. Conventional line commutated converters (LCC) are prone to occur commutation failure during faults, thus it is often used for point-to-point DC project rather than multi-terminal DC grids. Therefore, in recent years, most of the multi-terminal DC transmission systems studied are voltage sourced converter multi-terminal DC transmission (VSC-MTDC) and modular multi-level converter multi-terminal DC transmission (MMC-MTDC). But in the fixed power flow direction situation, conventional line commutated converter has lower investment and higher fault tolerance than voltage sourced converter, and forming a conventional line commutated converter based DC grids has lots of advantages. To solve the problems caused by commutation failure in conventional line commutated converter DC grids, this paper proposes a method by using fault current limiters (FCL). This method can guarantee the DC voltage and DC power of non-faulted converters be both stable during commutation failure. The concept and operation principle of the proposed method is simple and can be put into practical project conveniently. The correctness of the theoretical analysis is verified through simulations.